2016
DOI: 10.5534/wjmh.2016.34.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Korean Men: Results from the Fourth through Sixth Korean National Health and Nutrition Examination Surveys (2007~2014)

Abstract: PurposeObesity is related to many diseases, including urological conditions. We investigated the prevalence, risk factors, and treatment of male obesity.Materials and MethodsThis study included 17,485 men older than 20 years of age who participated in the fourth, fifth, and sixth administrations of the Korean National Health and Nutrition Examination Survey. Two main cutoff points for obesity were defined: a body mass index (BMI) ≥25 kg/m2 and a BMI≥30 kg/m2. Additionally, we defined obesity requiring pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…which ultimately lead to high calorie intake [3]. Men also tend to have lower body image dissatisfaction than women.…”
Section: Introductionmentioning
confidence: 99%
“…which ultimately lead to high calorie intake [3]. Men also tend to have lower body image dissatisfaction than women.…”
Section: Introductionmentioning
confidence: 99%
“…However, the second highest egg positive rate was reported in Chungcheongnam-do, where the GBC incidence rate is not as high [ 24 ]. Other studies have shown that the prevalence of obesity requiring pharmacotherapy was highest in regions with a low incidence rate of GBC, except for in Jeju [ 25 ]. Although obesity is a risk factor for GBC, its nationwide distribution is not associated with its distribution in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…These factors might improve our understanding of the prognostic value of obesity for RCC prognosis, although BMI is the most commonly used obesity index in clinical studies and real practice. Finally, we only considered Korean patients, and it is possible that there are ethnic or regional factors that affected our findings, which may not be representative of other ethnic groups and especially Western populations …”
Section: Discussionmentioning
confidence: 99%
“…Finally, we only considered Korean patients, and it is possible that there are ethnic or regional factors that affected our findings, which may not be representative of other ethnic groups and especially Western populations. 1,32…”
Section: Discussionmentioning
confidence: 99%